Linear and NLO Properties of Functional Group and Position Isomers of Azo and Azomethine: Comparative Photophysical‐Electrochemical Properties, Z‐Scan and DFT Studies. Issue 34 (10th September 2020) - Mishra, Virendra R.; Ghanavatkar, Chaitannya W.; Sharma, Suryapratap; Premarani, Aswathy; Mathew, Elizabeth; Joe, Isaac H.; Sekar, Nagaiyan
Abstract: Functional group and position isomers of azo and azomethine were selected to investigate their effect on linear and NLO properties. The azo and azomethine analogs show absorption maxima in the range 460–500 nm and 375–435 nm respectively. They are emissive in green, orange to the deep red region with a large Stokes shift of 100–200 nm. When we compared azo and azomethine chromophores i. e. functional group isomers, azo chromophore shows a bathochromic shift of 50–103 nm, while in case of position isomers azo and azomethine having larger conjugation effect i. e. VA‐2 and VI‐2 show a more bathochromic shift of 28 nm and 42 nm than the corresponding analogs VA‐1 and VI‐1, which show respectively 466 nm and 379 nm. Band gaps evaluated by electrochemical method and DFT method are correlated with the bathochromic shift in absorption maxima. The dyes are thermally stable (up to 280 °C). Open and closed aperture Z‐scan techniques were used to evaluate the third order non‐linear optical (NLO) parameters ‐ nonlinear absorptive coefficient (β), nonlinear refractive index (η2 ), and third order non‐linear optical susceptibility (χ (3) ). NLO properties were theoretically calculated by using DFT method with six different functionals. Mean absolute error (MAE) and standard deviation (SD) were evaluated to get more insight into theoretical calculation. With the set of calculated data points, MAE and SD calculated to check performance of the DFT functional. Different functionals were used to evaluate vertical excitation values and compared it with experimental absorption maxima. Abstract : Effect of functional group and position isomers of azo and azomethine on linear optical properties were evaluated.The red shift in absorption maxima is correlated with band gap calculated from electrochemical and DFT methods. The Third order non‐linear optical susceptibility (χ (3) ) were calculated from Z‐scan technique. Dyes shows reverse saturation absorption behavior due to two photon absorption mechanism. Vertical excitation and Non‐linear optical (NLO) properties were theoretically calculated by using DFT method with different functionals. Mean absolute error and standard deviation were used to identify the superior functional.